‘Shift’ Adaptation and a New Croatian Standard for Haavikko Developmental Stages’ Timing - Ivan Bedek; Jelena Dumančić; Tomislav Lauc; Miljenko Marušić; Ivana Čuković-Bagić (Acta Stomatologica Croatica)
Accurate age estimation is an integral part of the identification process. Although used infrequently when compared to more established methods, the Haavikko method can be used in cases where other dental age estimation methods have proven ineffective. Aim: The aim of this study was to adapt the Haavikko method as a means of improving age estimation on a representative sample of Croatian children and to establish an applicable standard for the Haavikko developmental stages. Material and methods: To achieve this objective, 1997 digital, standardized orthopantomograms of children aged 5 to 16 were collected in four Croatian cities. Drawing upon a previously published study of the Croatian population, a simple adaptation named ‘shift’ was introduced to the Haavikko method by adding the average difference between chronological and dental age to the estimated dental age. Squared deviations were used to compare the results of the original Haavikko method with the ‘shift’ adaptation. Accuracy of age estimation was presented as the percentage of correct estimations within intervals of ±0.5 years, ±1 year, ±1.5 years and ±2 years. The ‘shift’ adaptation was tested through simulation to assure population applicability. The average age for every stage of each permanent tooth was then calculated to provide Croatian specific tables for the Haavikko method. The ‘shift’ adaptation significantly improved age estimation accuracy among boys and girls in all age groups. Simulation confirmed the representativity of the sample and its population applicability. Conclusion: The Croatian specific tables comprise a standard when estimating age using the Haavikko method among Croatian children.